Hubungan Asupan Zat Gizi, Aktifitas Fisik, Lingkar Perut dan Persen Lemak Tubuh dengan Kadar Kolesterol Total Penderita Dislipidemia Rawat Jalan di RSUD dr. Doris Sylvanus Palangka Raya - Fretika Utami Dewi; Sugiyanto Sugiyanto (POLITEKNIK KESEHATAN KEMENKES PALANGKA RAYA, 2020)
Dyslipidemia can arise as a result of lifestyle changes. These lifestyle changes include smoking, lack of physical activity, alcoholism, a diet high in fat and less of dietary fiber. This study aims to determine the relationship of nutrient intake, physical activity, abdominal circumference and body fat percent with cholesterol levels of outpatients with dyslipidemia in RSUD dr. Doris Sylvanus Palangka Raya. The study design used a cross-sectional design with a purposive sampling method. The number of samples obtained was 48 people. Nutrient intake was obtained by the FFQ method and then analyzed with nutrisurvey, weight using digital scales, height using mikrotoice, physical activity using the Baecke form, abdominal circumference was measured using metline. Data were analyzed using the Pearson test. Results: The study show that the most of the samples were 50-59 years old, female with non-working status, moderate physical activity, abdominal circumference at risk category and thick fat percent with more category. The average intake of energy, protein, fiber are low, fat and carbohydrate intake are sufficient and the total cholesterol level are high. There was no significant relationship between energy intake (P = 0.404), protein intake (P = 0.765), carbohydrate intake (P = 0.876), fiber intake (P = 0.498), physical activity (P = 0.277), abdominal circumference (P = 0.737), percents body fat (P = 0.755) with total cholesterol levels, but fat intake was significantly related (P = 0.001)